Semi‐automated biobank sample processing with a 384 high density sample tube robot used in cancer and cardiovascular studies. Issue 1 (14th August 2015) - Malm, Johan; Lindberg, Henrik; Erlinge, David; Appelqvist, Roger; Yakovleva, Maria; Welinder, Charlotte; Steinfelder, Erik; Fehniger, Thomas E; Marko‐Varga, György
Abstract: Background: In the postgenomic era, it has become evident that analysis of genetic and protein expression changes alone is not sufficient to understand most disease processes in e.g. cardiovascular and cancer disease. Biobanking has been identified as an important area for development and discovery of better diagnostic tools and new treatment modalities. Biobanks are developed in order to integrate the collection of clinical samples from both healthy individuals and patients and provide valuable information that will make possible improved patient care. Modern healthcare developments are intimately linked to information based on studies of patient samples from biobank archives in large scale studies. Today biobanks form important national, as well as international, networks that share and combine global resources. Methods: We have developed and validated a novel biobanking workflow process that utilizes 384‐tube systems with a high speed sample array robot with unique processing principles. Results: The 384‐tube format and robotic processing is incorporated into a cancer and cardiovascular diagnostic/prognostic research program with therapeutic interventions. Our biobank practice has gained acceptance within many hospitals and research units and is based on high‐density sample storage with small aliquot sample volumes. The previous standard of 5–10 mL sample volume tubes is being replaced by smaller volumes of 50–70 μL blood fractions that typically result in hundreds of thousands of aliquot fractions in 384‐tube systems. Conclusions: Our novel biobanking workflow process is robust and well suited for clinical studies.